The investigation of exact solutions of nonlinear time-fractional Klein-Gordon equation by using generalized Kudryashov method - Demiray, Seyma Tuluce; Pandir, Yusuf; Bulut, Hasan (American Institute of Physics Inc., 2014)
In this study, we consider exact solutions of nonlinear time-fractional Klein-Gordon equation by using generalized Kudryashov method (GKM). The nonlinear time-fractional Klein-Gordon equation can be converted into nonlinear ordinary differantial equation by transformation. Consequently, GKM has been implemented to find exact solutions of nonlinear time-fractional Klein-Gordon equation and we obtain some new solutions such as soliton solutions and hyperbolic function solutions. Moreover, we point out that this method is a generalized form of classical Kudryashov Method. © 2014 AIP Publishing LLC.
10th International Conference on Mathematical Problems in Engineering, Aerospace and Sciences, ICNPAA 2014 -- 15 July 2014 through 18 July 2014 -- Narvik -- 112237
Keywords: Generalized Kudryashov Method; Hyperbolic Function Solutions; Nonlinear Time-Fractional Klein-Gordon Equation; Soliton Solutions